Penerapan Digital Marketing pada Usaha Basreng Basgoy di Bengkalis - Aldo Vika Wiranda; Tri Handayani (Politeknik Kampar, 2025)
This community service activity, entitled Implementation of Digital Marketing on Basreng Basgoy Business, aims to analyze the SWOT factors (Strengths, Weaknesses, Opportunities, Threats), determine the STP strategies (Segmenting, Targeting, Positioning), and evaluate the implementation of the marketing mix strategy used by the Basreng Basgoy business in Bengkalis. Furthermore, this program seeks to examine the effectiveness of digital marketing in improving marketing strategies and expanding consumer reach, as well as to identify challenges and solutions encountered during the implementation process. The method used consists of planning, implementation, and evaluation stages conducted directly with the business owner. The results show that digital marketing implementation has significantly improved business performance through various online platforms such as Instagram, WhatsApp, and Shopee. Consistent promotion and engaging content creation successfully increased consumer interaction and product sales. Challenges encountered include tight market competition and limited content ideas. The solutions applied involve strengthening branding by emphasizing product uniqueness, improving promotional visuals, and conducting continuous content analysis and optimization.